Long-Run Links Among Money, Prices, and Output: World-Wide Evidence - Hans-Eggert Reimers; Helmut Herwartz (Deutsche Bundesbank, 2001)
Regarding inflation as being a monetary phenomenon in the long-run is a widely-held view in modern macro economics. We analyse this topic by means of a P-star model. Based on the quantity theory of money, this approach explains inflation via a supposed equilibrium price level (P-star), which itself depends on potential output and money. We investigate country-specific models for 110 economies, and also a pooled system thereof. We test for cointegration among money, prices, and real output. Moreover, parameter restrictions for the long-run relationships implied by the monetary theory are tested. Country specific P-star variables are constructed and the cointegration property between prices and the P-star variable is analysed. Along these lines, we find that actual prices and their P-star counterparts are cointegrated at the pooled level and thus demonstrate the importance of money for the development of prices. – – Die Aussage, dass Inflation langfristig ein monetäres Phänomen ist, ist eine grundlegende Erkenntnis der Makroökonomie. Dieser Sachverhalt wird in dieser Arbeit im Rahmen eines P-Stern-Modells analysiert. Ausgehend von der Quantitätstheorie des Geldes erklärt der P-Stern-Ansatz die Inflationsrate mit Hilfe eines berechneten Gleichgewichtspreisniveaus (P-Stern), das vom Produktionspotential und von einer Geldmenge abhängt. Wir untersuchen länderspezifische Modelle für 110 Volkswirtschaften und ein aus den Gleichungen bestehendes gepooltes System. Es wird auf Kointegration zwischen einer Geldmenge, einem Preisniveau und dem realen Output testet. Weiterhin werden die Parameterrestriktionen, die sich durch die monetare Theorie ergeben, für die langfristige Beziehung überprüft. Zusätzlich werden nationale P-Stern- Variablen konstruiert und es wird auf Kointegration zwischen diesen und den Preisen getestet. Im empirischen Teil finden wir, wenn die Variablen gepoolt werden, dass die aktuellen Preisniveaus mit den dazugehörenden P-Stern-Variablen kointegriert sind. Dies verdeutlicht die Wichtigkeit des Geldes für die Entwicklung der Preise.
Keywords: E31; C22; 330; Quantity theory of money; Panel cointegration analysis; Wild bootstrap inference; Geldmenge; Preisniveau; Konjunktur; Quantitätstheorie; P-Star; Kointegration; Schätzung; Welt